2012
DOI: 10.1590/s0100-40422012000200031
|View full text |Cite
|
Sign up to set email alerts
|

A validated method using RP-HPLC for quantification of reserpine in the Brazilian tree Rauvolfia sellowii Müll. Arg. (Apocynaceae)

Abstract: Recebido em 26/4/11; aceito em 13/7/11; publicado na web em 19/8/11This study describes a simple, fast and reproducible method using RP-HPLC-UV, in a gradient system, for quantification of reserpine in Rauvolfia sellowii stem bark. The analysis were carried out on a C18 column; mobile phase was water and acetonitrile, and separations were carried out in 10 min, flow rate of 1.0 mL min , and the mean recovery was 95.1%. The amount of reserpine found in the dried stem bark was 0.01% (m/m).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…They observed that the reserpine content was ranged from 0.0382 to 0.1442%. Baratto et al (2012) quantified reserpine content in the dried stem bark of R. sellowii by HPLC and found 0.01% dry weight basis.…”
Section: Resultsmentioning
confidence: 99%
“…They observed that the reserpine content was ranged from 0.0382 to 0.1442%. Baratto et al (2012) quantified reserpine content in the dried stem bark of R. sellowii by HPLC and found 0.01% dry weight basis.…”
Section: Resultsmentioning
confidence: 99%
“…High-performance liquid chromatography (HPLC) has been successfully applied to analyze plant extracts and products. [ 13 14 ] This method has several advantages, such as efficient separation, identification and quantification of similar compounds. However, to the best of our knowledge, no HPLC-UV simultaneous method has been reported to evaluate extracts and products from S. terebinthifolius .…”
Section: Introductionmentioning
confidence: 99%
“…Multiple herbs in polyherbal and herbo-mineral formulations in a meticulous ratio will give an improved therapeutic effect and lessening the toxicity. [4,5] Several chromatographic methods, for example, UV-visible Spectrophotometric, [4][5][6] HPLC, [7][8][9][10] HPTLC, [11][12][13][14][15][16] and methods are established for the qualitative and quantitative estimation of the Ascorbic acid, Gallic acid, Quercetin, and Reserpine separately or together with other chemical markers. This study primarily reports RP-HPLC method for the straightforward and rapid determination of the Ascorbic acid, Gallic acid, Quercetin, and Reserpine in Polyherbal Formulation.…”
mentioning
confidence: 99%